Cover Jurnal Fitopatologi Vol. 18 No. 1, Januari 2022 - Hidayat, Sri Hendrastuti (Jurnal Fitopatologi Indonesia, 2022)
This editorial contains the front cover, editorial page, and back cover of the Indonesian Journal of Phytopathology Vol. 18 No. 1, Januari 2022